The southern distribution limit of the lynx (Lynx lynx) in the Middle Dnipro region: factors of advance and restriction - Zagorodniuk, I.; Nikolaichuk, O. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2025)
An analysis of the southern distribution limit of the lynx in the Middle Dnipro region, in the area from Zhytomyr to Nizhyn, i.e. in the Ukrainian part of Polissia known as Prydniprovske Polissia, is presented. This area is a zone of natural growth in abundance and expansion of the species' range and represents an important model for analysing the potential of indicator species in the Polissia natural zone to restore their former presence and role in the faunal communities of the Polissia. In total, the southern range of the lynx in the region is described in 17 locations, most of which are the southernmost for the entire Polissia segment of the lynx's geographical range within Ukraine. All locations where the species has been recorded, delineating the southern edge of its range, are in areas where the lynx had not been known to occur previously. The analysis includes only data on findings of the species in the last 25 years, and all such marginal findings are essentially new, dating no earlier than 2010–2020. This is a result of the growing lynx population in the Polissia and shows how the species is spreading in the region. Factors limiting and supporting population growth and species expansion into new areas are considered. The three key supporting factors are the development of the food base, a decrease in anthropogenic pressure, and the presence of natural eco-corridors with powerful natural cores covering an area of 1–2 thousand hectares. An important factor in the population growth and dispersal of the lynx was the high (restored) abundance of species that are potential prey for the lynx, primarily roe deer and wild boar. One of the triggers for the restoration of the geographical ranges of large mammals in the Polissia region, including the lynx, was the significant reduction of human impact on the natural complexes of Central Polissia, a substantial decrease in economic activity and the virtual cessation of hunting (and, to a certain extent, poaching), which was essentially facilitated by the existence of the Chernobyl Exclusion Zone, the war in Ukraine, and the resulting increased control of frontier areas, as well as significant restrictions on any human activity in forested areas. If the current minimum levels of anthropogenic pressure on the region's natural complexes are maintained, the species may advance southward by another 50–70 km.